2011
DOI: 10.1097/pcc.0b013e3181f53147
|View full text |Cite
|
Sign up to set email alerts
|

U.S. attitudes and perceived practice for noninvasive ventilation in pediatric acute respiratory failure

Abstract: Noninvasive positive-pressure ventilation is widely used and most frequently utilized in patients with acute lower airway disease. Factors such as severe defects in oxygenation and ventilation, disease progression, and patient tolerability decreased the likelihood of use. These findings may help direct further studies of noninvasive positive-pressure ventilation in children with acute respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Despite the growing use of this therapy, there are few prospective controlled trials in pediatrics that might guide the clinician in determining indications and strategies for the use of NPPV (4,5). Additionally, many studies of NPPV in children include all children with acute respiratory failure and do not differentiate between PARDS and other etiologies.…”
mentioning
confidence: 99%
“…Despite the growing use of this therapy, there are few prospective controlled trials in pediatrics that might guide the clinician in determining indications and strategies for the use of NPPV (4,5). Additionally, many studies of NPPV in children include all children with acute respiratory failure and do not differentiate between PARDS and other etiologies.…”
mentioning
confidence: 99%
“…Previous studies showed variable rates of NIV use in these clinical scenarios. While Tume et al reported a 52% use ‘to avoid intubation, Fanning et al found 81% of participants reporting a willingness to use NIV in high‐risk extubation failure. Fioretto et al did not find any significant difference between NIV (delivered by means of a face or nasal mask and a conventional ventilator) and standard oxygen therapy after extubation.…”
Section: Discussionmentioning
confidence: 99%
“…In a large Italian study, asthma represented the less frequent condition treated with NIV . Fanning et al reported a 51% use of NIV in asthma among physicians in the United States who responded to a survey about the use of NIV in pediatric ARF. A retrospective study in the United States analyzing fatal and near‐fatal asthma from 2005 to 2009 reported a 16% use of NIV prior to intubation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population of pediatric critical care professionals, which can be identified, is approximately 1,000 (9). The 10% to 12% population sample in this current study is too small to reliably determine if the results obtained are valid.…”
mentioning
confidence: 85%